Students’ technology acceptance of computer-based applications for analyzing animal behavior in an out-of-school lab - Henrich, Marvin; Formella-Zimmermann, Sandra; Gübert, Jennifer; Dierkes, Paul W. (Frontiers in Education, 2023)
Behavioral biology is a field that students find fascinating. To get the most out of the various benefits of teaching it, a practical approach should be followed. One way to do this is to use video recordings of animals and different software to analyze those recordings. However, learners will not benefit from this approach if they do not choose to actually use the provided technology. This makes it of critical importance to assess learners' acceptance of software in the field of behavioral biology. By applying the Technology Acceptance Model (TAM), we investigated students' acceptance of authentic behavior evaluation software and possible factors influencing this. For this purpose, 171 students were questioned at an out-of-school student lab called "KILab". In addition, potential effects of the student lab on attitudes toward artificial intelligence and technology affinity were examined. The results show a high technology acceptance towards the software and a dependence of this on the factors technology affinity and acceptance towards artificial intelligence. Furthermore, the use of the software has a positive impact on the self-assessment of technology affinity and attitude towards artificial intelligence. Thus, this study shows that the use of video recordings and software for behavior analysis is generally suitable for educational use and can be a possible extension of the hands-on implementation of behavioral science education.